Effect of non-invasive brain stimulation on post-stroke cognitive impairment: a meta-analysis - Zhao, Jing; Meng, Qian; Qi, Shuo; Zhao, Hongfei; Xia, Ling (Frontiers in Neurology, 2024)
Background Previous studies have suggested that repetitive transcranial magnetic stimulation (rTMS) may be an effective and safe alternative treatment for post-stroke cognitive impairment (PSCI). Similarly, the application of transcranial direct current stimulation (tDCS) during stroke rehabilitation has been shown to improve cognitive function in PSCI patients. However, there have been conflicting results from some studies. Therefore, this study aims to conduct a meta-analysis to evaluate the effects of tDCS and rTMS on PSCI. Methods The meta-analysis search for articles published from the initial availability date to 5 February 2024 in databases. The extracted study data were entered into STATA 12.0 software for statistical analysis. Results This meta-analysis provides evidence that both rTMS and tDCS have a positive impact on general cognitive function in PSCI patients [immediate effect of rTMS: standard mean difference (SMD) = 2.58, 95% confidence interval (CI) = 1.44 to 3.71; long-term effect of rTMS: SMD = 2.33, 95% CI = 0.87–3.78; immediate effect of tDCS: SMD = 2.22, 95% CI = 1.31–3.12]. Specifically, rTMS was found to significantly improve attention, language, memory, and visuospatial functions, while it did not show a significant therapeutic effect on executive function (attention: SMD = 3.77, 95% CI = 2.30–5.24; executive function: SMD = −0.52, 95% CI = −3.17–2.12; language: SMD = 3.43, 95% CI = 1.50–5.36; memory: SMD = 3.52, 95% CI = 1.74–5.30; visuospatial function: SMD = 4.71, 95% CI = 2.61–6.80). On the other hand, tDCS was found to significantly improve executive and visuospatial functions but did not show a significant improvement in attention function and memory (attention: SMD = 0.63, 95% CI = −0.30–1.55; executive function: SMD = 2.15, 95% CI = 0.87–3.43; memory: SMD = 0.99, 95% CI = −0.81–2.80; visuospatial function: SMD = 2.64, 95% CI = 1.04–4.23). Conclusion In conclusion, this meta-analysis demonstrates that both rTMS and tDCS are effective therapeutic techniques for improving cognitive function in PSCI. However, more large-scale studies are needed to further investigate the effects of these techniques on different cognitive domains in PSCI.